Risk factors for small bowel bacterial overgrowth and diagnostic yield of duodenal aspirates in children with intestinal failure: a retrospective review - Gutierrez, Ivan M. (2012)
BACKGROUND: Children with intestinal failure (IF) are at risk of small bowel bacterial overgrowth (SBBO) due to anatomic and other factors. We sought to identify risk factors for SBBO confirmed by quantitative duodenal culture. METHODS: A single center retrospective record review of children who had undergone endoscopic evaluation for SBBO (defined as bacterial growth in duodenal fluid of >10(5) CFU/mL) was performed. RESULTS: We reviewed fifty-seven children with median (25–75(th)%) age 5.0 (2.0–9.2) years. Diagnoses included motility disorders (28%), necrotizing enterocolitis (16%), atresias (16%), gastroschisis (14%), and Hirschprung’s disease (10.5%). Forty patients (70%) had confirmed SBBO. Univariate analysis showed no significant differences between patients with and without SBBO for the following variables: age, sex, diagnosis, presence of ileocecal valve, and antacid use. Patients receiving parenteral nutrition (PN) were more likely to have SBBO (70% vs. 35%, P = .02). Multiple logistic regression analysis confirmed that PN administration was independently associated with SBBO (adjusted OR= 5.1; adjusted 95% CI 1.4–18.3, P = .01). SBBO was not related to subsequent risk of catheter-related blood stream infection. CONCLUSION: SBBO is strongly and independently associated with PN use. Larger, prospective cohorts and more systematic sampling techniques are needed to better determine the relationship between SBBO and gastrointestinal function.